PEMBUATAN ALAT PENGHASIL BIOGAS SEDERHANA DI KAMPUNG HAWAI KABUPATEN JAYAPURA - Ilham Salim; Frans Kafiar (JURNAL PENGABDIAN PAPUA, 2017)
Biogas is a gas produced from the process of decomposition of organic materials by microorganisms in rare oxygen (anaerobic) conditions. Biogas component: ± 60% CH (methane), ± 38% CO (carbon dioxide), ± 2% N2 , O2 , H2 , and H2 S2. Biogas materials in this service comes from cow dung. Cow manure is a substrate that is considered most suitable as a source of biogas, because the substrate already contains methane as source of energy. In addition to cattle dung biogas can also reduce environmental pollution because it produced a more environmentally friendly energy source. In Kampung Hawai, Jayapura Regency, some of people have been doing cattle ranching activities. The waste in the form of fresh cow dung has not been utilized for the manufacture of biogas as an alternative energy source.The purpose of this devotional activity was to utilize fresh cow dung as a biogas energy source by creating simple biogas generator tools with cheap and easy equipment. The method used with the ratio of cow dung and water, 1:1 and also the addition of EM4 (Effective microorganisms) in the mixture of 5%, 7.5%, 10%; and 12.5% with fixed volume in the digester. The results of this activity obtained biogas which can be made by using a simple tool with respect to the ratio of mixture cow dung and water. Addition of EM4 affects the fermentation reaction in the digester to produce biogas. The highest biogas production was obtained in the addition of EM4 by 10% with the highest produced pressure and obtained quite significantly starting on the 12th day. The cattle ranchers at this location was interested in this devotion activity and will continue to apply the technology of making biogas that has been informed and understood. Keywords: Biogas, Cow Manure, EM4, Pressure